Theological Talk in a Salsa Bar on Wigan Pier. (January 2020) - Greenough, Chris
Is bringing together Sarah Coakley and Marcella Althaus-Reid like mixing oil and water? An encounter between a systematic theologian and a contextual, queer theologian might seem artificial, but this article offers critical insights into the work of both scholars, revealing similarities within the tropes of their theological thinking. Aside from navigating sites of possible parallels and conflict between their work, this article springboards their settings by offering a new location – a salsa bar on Wigan Pier – to be able to do theology. Academic writing is largely characterized by adherence to rigour, order and structure but the whole point of queer is to disturb and disrupt established norms. Therefore, by mobilizing the work of Judith Halberstam, this article offers a rich dialogue combining scholars working in gender and sexualities in the form of a play script. Critical commentary on the play text demonstrates the necessity to continue to subvert dominant repetitions in theology.